Integrasi Kecerdasan Buatan dalam Penulisan Buku Akademik: Model Pengembangan Kompetensi Dosen Berkelanjutan - Astri Rumondang Banjarnahor; Juliater Simarmata; Yulianti Keke; Euis Saribanon; Reni Dian Octaviani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service program aims to enhance lecturers’ competence in book writing assisted by Artificial Intelligence (AI) as part of strengthening the implementation of the Tri Dharma Perguruan Tinggi. The training was conducted at the Institute of Transportation and Logistics Trisakti through a participatory approach encompassing five integrated stages: needs analysis, module development, online training implementation, intensive mentoring, and evaluation with follow-up actions. The results demonstrated significant improvement in participants’ understanding of academic book structure and writing techniques, writing speed, and confidence in utilizing AI as a creative partner (co-writer). AI was proven to play a strategic role in idea formulation, manuscript editing, reference management, and enhancing the quality of academic language. However, challenges related to ethical AI usage, academic integrity, and digital literacy remain essential areas for improvement. Overall, this training contributes to developing a productive, ethical, and sustainable digital literacy ecosystem in academia and serves as an innovative model for strengthening lecturers’ capacities toward higher education transformation in the digital era.